The morphology and morphometrics of lymph nodes of sheep and lambs: a study of normal sheep and those with arthritis : a thesis presented in partial (20%) fulfilment of the degree of Master of Philosophy in Veterinary Pathology and Public Health at Massey University, New Zealand - Yao, Shutang (Massey University, 1986)
During the history of man, the most serious meat borne diseases were probably trichinellosis and tuberculosis. Owen was the first person to recognize Trichinella spirallis (Hoeden, 1964) and Koch the first to isolate Mycobacterium tuberculosis (Martin, 1978) in 1835 and 1882 respectively. These diseases had been a major cause of human morbidity and mortality for many centuries before the infectious agents were described. It is interesting to note that lesions of tuberculosis were found in mummies of the Rameses dynasties which are some 30 centuries old and human trichinellosis occurred in early epochs of European civilization without it being realised. With the development of modern concepts of disease, greater attention was paid to the source and handling of meat for human consumption (Brandly, Migaki and Taylor, 1966). Since meat is an essential source of human food, a knowledge and understanding of potential meat borne diseases is necessary. It has become accepted that meat inspection is an indispensable branch of meat hygiene in relation to the control of meat borne diseases.
Keywords: Lymph nodes; Veterinary anatomy; Sheep; Lambs; Diseases; Arthritis